EKSTRAKSI FLAVONOID DARI TANAMAN OBAT SEBAGAI ANTI OKSIDAN - Haryono, Gogot (Journal TECHNO, 2015)
Flavonoids are phenolic compounds found in many plants and some species canact as antioxidants. Antioxidants are a substance very easily oxidized, so that when thereis an air / oxygen would oxidize antioxidants first before oxidize other substances.Penilitian result of various crops showed varying levels of antioxidants in each plant.This study aims to determine the levels of flavonoids in several medicinal plants arewidely consumed by humans is the parasite tea, red betel leaves, soursop leaves, fruit andleaves of gotu kola gods crown. From the research results for the five materials tested,mistletoe tea has the highest concentration of flavonoids. Research carried out by theextraction time of 120 minutes, the concentration of ethanol 96%, stirrer speed of 300rpm and a temperature of 70 ° C solution obtained parasite tea flavonoid concentrationof 0.575 g / L, the mass transfer coefficient (Kca) is calculated based on the results ofexperiments for the extraction of tea flavonoids parasite 0.00863382 min-1.Keywords: flavonoids, extraction, plant